Analisis Efektifitas Program Bantuan Pangan Nasional dalam Meningkatkan Kesejahteraan Rumah Tangga Miskin di Indonesia - Ade Asminaria Sihombing; Divo Valentino Siboro; Excaudia Siringo-ringo; Josua Arnaldo Pane; Pintar Rohsangapta Padang (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
The National Food Assistance Program (Non-Cash Food Assistance/BPNT) is one of the social policy instruments designed by the Indonesian government to enhance food security and improve the welfare of poor households. This research aims to analyze the effectiveness of this program by assessing its accessibility, targeting accuracy, commodity quality, and its impact on household expenditure and stability of food consumption.The research methodology uses a descriptive-analytical approach, combining secondary data from official government reports and academic literature with primary data in the form of a limited survey of beneficiaries.The results of the analysis indicate that the program is quite effective in increasing poor households' access to staple foods, primarily through the more transparent and flexible non-cash distribution mechanism. However, several constraints are still found, including inaccurate targeting of beneficiaries, variation in food quality at the e-warung level, and the limited digital literacy of some households.Nevertheless, the program is proven to be able to reduce the burden of food expenditure and improve consumption quality, thereby contributing positively to the welfare of poor households. This research suggests improving the validation of beneficiary data, supervising distribution, and expanding food and digital education for the community to further optimize the program's effectiveness.